Early-Life Interpersonal and Affective Risk Factors for Pathological Gaming - Bussone, Silvia; Trentini, Cristina; Tambelli, Renata; Carola, Valeria (Frontiers in Psychiatry, 2020)
Internet gaming is among the most popular entertainment options, worldwide; however, a considerable proportion of gamers show symptoms of pathological gaming. Internet gaming disorder (IGD) has been proposed to describe a behavioral addiction, which shares many similarities, both physical and psychological, with substance use disorder. Environmental factors, such as interpersonal and relationship dynamics during childhood and adolescence, have been suggested to modulate the onset and trajectories of IGD. However, studies exploring the contributions of dysfunctional family environments to the development of IGD remain limited. This minireview aims to offer an overview of the current knowledge regarding the impacts of early-life interpersonal and relationship dynamics on the development of IGD and to provide a snapshot of the current state of the literature in this field. Specifically, it underlines the modulatory role of early-life relational factors such as (a) family function, (b) parent-child relationships, (c) childhood maltreatment, and (d) bullying and cyberbullying on the development of IGD. Consistent with this evidence, therapeutic interventions that aim to “restructure” the emotional ties and familiar dynamics that are known to be associated with dysfunctional behaviors and feelings, and likely promote pathological gaming, are recognized as the most successful clinical therapeutic approaches for IGD.